Effect of garnet incorporation on the functional properties of sunscreens - CHAKARTNARODOM, Parinya; MUNMANI, Kanyarat; POLSILAPA, Sureerat; CHAYSUWAN, Duangrudee; PRAKAYPAN, Wichit; SONPRASARN, Passakorn; LAITILA, Edward; KONGKAJUN, Nuntaporn (Journal of Metals, Materials and Minerals, 2026)
Garnet, a silicate mineral, was investigated as a replacement for the TiO2-based compound in sunscreen formulations. Samples containing garnet were evaluated for color shade, viscosity, sun protection factor (SPF), and water resistance. Substituting the TiO2-based compound with garnet reduced both viscosity and SPF but markedly enhanced water resistance. This improvement is attributed to the physical reinforcement provided by garnet particles, which strengthen the sunscreen film and reduce wash-off under water exposure. Garnet incorporation also altered the product’s appearance from white to a darker brownish-beige tone, improving visual compatibility with a wider range of skin tones.